2015
DOI: 10.1163/15685403-00003436
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prey species and concentration on egg production efficiency and hatching success in Acartia tonsa Dana (Copepoda, Calanoida)

Abstract: We measured ingestion rate (IR), egg production rate (EPR) and egg hatching success (EHS) at increasing prey concentrations and calculated egg production efficiency (EPE) and maintenance rate (MR) in the estuarine copepod Acartia tonsa fed three different algal diets. EPR and EHS were relatively more affected by prey species than by prey concentration. EPEs were constant among carbon concentrations (C) on a diet of Rhodomonas baltica (0.202 ± 0.055, mean ± SD) and Dunaliella tertiolecta (0.034 ± 0.015), but de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…It is well-established that egg production rate is higher when the food is obtained from nutrient-enriched or other optimized environments (Kleppel et al, 1998). Our results are generally in agreement with early observations which showed higher egg production rates in A. tonsa at higher food quantities (Jónasdóttir, 1994;Gusmão and McKinnon, 2009;Acheampong et al, 2011;Wendt and Thor, 2015), or at higher food qualities (lower food C:N ratios) (Kiørboe, 1989). In contrast, nonsignificant changes or a decrease in egg production rates were also found with increasing dietary C:N in A. tonsa (Jónasdóttir, 1994;Augustin and Boersma, 2006).…”
Section: Egg Production Rates In Acartia Tonsasupporting
confidence: 92%
See 1 more Smart Citation
“…It is well-established that egg production rate is higher when the food is obtained from nutrient-enriched or other optimized environments (Kleppel et al, 1998). Our results are generally in agreement with early observations which showed higher egg production rates in A. tonsa at higher food quantities (Jónasdóttir, 1994;Gusmão and McKinnon, 2009;Acheampong et al, 2011;Wendt and Thor, 2015), or at higher food qualities (lower food C:N ratios) (Kiørboe, 1989). In contrast, nonsignificant changes or a decrease in egg production rates were also found with increasing dietary C:N in A. tonsa (Jónasdóttir, 1994;Augustin and Boersma, 2006).…”
Section: Egg Production Rates In Acartia Tonsasupporting
confidence: 92%
“…As food concentration increased, K C /K N increased at higher algal C:N ratios (N-deficient diets) and showed a unimodal response at lower algal C:N ratios, while K C /K P increased over the entire range of algal C:P ratios in our study (Table 3 and Figure 3). Previous studies have shown variable response patterns of GGE to increasing food concentrations in zooplankton, e.g., positive responses in the copepod Eudiaptomus graciloides (Hamburger and Boētius, 1987), Cyclops vicinus (Santer and van den Bosch, 1994) and Daphnia (Anderson et al, 2005), negative responses in A. tonsa (Kiørboe et al, 1985;Wendt and Thor, 2015), the cladoceran Penilia avirostris (Atienza et al, 2007) and the copepod Oithona davisae (Almeda et al, 2010b), and nonsignificant changes in A. tonsa (Wendt and Thor, 2015). Such variations in zooplankton GGE responses to food concentrations can be explained by differences in nutrient quality of food (e.g., algal C:N and C:P ratios in the present study; Straile, 1997;Bukovinszky et al, 2012), prey species (Wendt and Thor, 2015), development stages of zooplankton (Almeda et al, 2010a), methodological protocols (Straile, 1997), as well as withinpopulation genetic variance in the metabolic rate (Einum et al, 2019).…”
Section: Limitation Strength Of Elements and Efas In Acartia Tonsamentioning
confidence: 99%
“…Copepods show strong functional responses, and significant increases in both metabolic rate and RNA/DNA ratio with prey concentration are not surprising [3840]. Such observations may provoke the conclusion that future OA effects will be masked by much stronger variations caused by natural temporal and spatial variability of prey concentrations.…”
Section: Discussionmentioning
confidence: 99%